Design Parameters Investigation of Single Mode Silicon-on-Insulator (SOI) Microring Channel Dropping Filter - Haroon, Hazura; Hanim, Abdul Razak; Mardiana, Bidin; Shaari, Sahbudin; majlis , B.Y; Menon, P.S (American Scientific Publishers, 2013)
Microring resonators (MRR) have been extensively explored due to the high quality factor, compact size and easy integration of fabrication. By tailoring microring dimensions, resonator can be tuned to support the desired spectrum of optical modes. This enhancing the development of new types of planar lightwave circuits (PLC) devices for wavelength-division-multiplexed (WDM) networks such as optical filters, sensors, modulators and switches. In this paper, we carry out a quick analysis to investigate a MRR based wavelength filter which will be working around 1.55 μm wavelength. In order to design an excellent MRR filter, optimization of the design parameters are crucial. The FDTD simulation by RSoft is employed to design and characterized the wavelength filter performance. Optimization of design parameters such as size of rings and channels, resonant order, radii of microring and gap size are determined. Multiple serially cascaded microrings are also studied. The device is designed to satisfy single mode behavior for small SOI waveguide. Optimum device parameters are obtained and the key issues affecting the resonator design such as free spectral range (FSR), insertion loss and Quality Factor (Q-factor) are discussed.